2015
DOI: 10.1186/s13046-015-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Skin-reducing mastectomy and immediate breast reconstruction in patients with macromastia

Abstract: IntroductionIn women with macromastia, a type IV skin sparing mastectomy is often required to achieve an aesthetically pleasing reconstruction. The introduction of “skin-reducing mastectomy”, which inserts a permanent prosthetic device into a large pouch made by the pectoralis major muscle and an inferior pedicle dermal flap, allows the surgeon to achieve a safe oncologic result plus a cosmetically satisfying reconstruction.ObjectiveWe report here our experience with the skin-reducing mastectomy with the aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“… 21 , 31 In our study, average permanent implant volume was 550cc with a high of 700cc, without any implant loss or major complication. In contradistinction, De Vita et al 32 reported an average implant volume of 478cc utilizing a Wise pattern SRM and had a significant major complication rate of 29%. Irwin et al 21 obtained a 420cc median fill with partial submuscular Wise pattern DTI reconstruction but had an implant failure rate of 3.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 31 In our study, average permanent implant volume was 550cc with a high of 700cc, without any implant loss or major complication. In contradistinction, De Vita et al 32 reported an average implant volume of 478cc utilizing a Wise pattern SRM and had a significant major complication rate of 29%. Irwin et al 21 obtained a 420cc median fill with partial submuscular Wise pattern DTI reconstruction but had an implant failure rate of 3.8%.…”
Section: Discussionmentioning
confidence: 99%
“…As our goal was to ascertain safety with a novel skin excision, we excluded patients with certain known risk factors for reconstruction failure, such as active nicotine use, 37 BMI >35, 33 and previous history of breast radiation. 38 However, other known risk factors were not excluded and were represented in our cohort: breast weight >600 g, 5 , 22 , 39 , 40 age greater than 65, 41 bilateral reconstructions, 42 , 43 immediate DTI reconstructions, 34 BMI >30, 33 , 42 implant volume >500cc, 32 ADM, 44 patients requiring PMRT, 38 , 45 and invasive breast disease. 46 …”
Section: Discussionmentioning
confidence: 99%
“…The use of SurgiMend was also described after skin-reducing mastectomy in patients needing a very large implant, for which dermal and anterior serratus flaps were inadequate (De Vita et al, 2015). Generally, the use of acellular dermal matrix had been reserved for patients who have undergone previous breast surgery such as quadrantectomy, for patients with extremely high insertions of their pectoralis muscle, and for patients needing a large breast implant or large pouch.…”
Section: © 2020 Ma Healthcare Ltdmentioning
confidence: 99%
“…De Vita y col. consideran este procedimiento como la técnica más adecuada para la reducción de riesgo de padecer cáncer mamario en pacientes con macromastia. (15) La MIVAP permite realizar la mastectomía reductora de riesgo, la reducción y la reconstrucción mamaria en un solo tiempo quirúrgico, cumpliendo adecuadamente con los 3 objetivos cuyo beneficio redunda en una menor cantidad de actos quirúrgicos y/o anestésicos, menos periodos de inactividad laboral y mejor recuperación de los tejidos tras una única intervención. (16)…”
Section: Complicacionesunclassified